Whole-Genome Identification and Comparative Expression Analysis of Anthocyanin Biosynthetic Genes in Brassica napus - He, Dan; Zhang, Dawei; Li, Ting; Liu, Lili; Zhou, Dinggang; Kang, Lei; Wu, Jinfeng; Liu, Zhongsong; Yan, Mingli (Frontiers in Genetics, 2021)
Anthocyanins contribute to the most colors of plants and play protective roles in responses to abiotic stresses. The Brassica napus is widely cultivated worldwide as both oilseed and vegetable. However, only several high anthocyanin-containing cultivars have been reported and the mechanisms of anthocyanin accumulation have not been well elucidated in B. napus. Here, phenotype, comparative whole-genome identification and genes expression analysis were performed to investigate the dynamic change of anthocyanin content and the gene expression patterns of anthocyanin biosynthetic genes (ABGs) in B. napus. A total of 152 ABGs were identified in the B. napus reference genome. To screen out the critical genes involving in anthocyanin biosynthesis and accumulation, the RNA-seq of young leaves of two B. napus lines with purple leaves (PL) or green leaves (GL), and their F1 progeny at 41, 91 and 101 days were preformed to identify the differentially expressed genes. The comparative expression analysis of these ABGs indicated that the up-regulation of TT8 together with its target genes (such as DFR, ANS, UFGT and TT19) might promote the anthocyanin accumulation in PL at the early developmental stage (41 to 91 d). While the down-regulation of those ABGs and anthocyanin degradation at the late developmental stage (91 to 101 d) might result in the decrease of anthocyanin accumulation. Our results would enhance the understanding of the regulatory network of anthocyanin dynamic accumulation in B. napus.